Visualizing Range and Alibi Queries for Space-Time Prisms of Uncertain Moving Objects - Thoms, Nathan; Cook, Ryan; Prochaska, Mara; Jorgensen, Eric; Trajcevski, Goce (Proceedings / IEEE International Conference on Mobile Data Management, 2025)
One important "fact of life" when modeling motion, especially when it comes from real location-in-time data sources, is the uncertainty of the objects' whereabouts at a given time instant. Different models have been proposed in the literature and their impacts have been considered on algorithms for processing various spatio-temporal (continuous as well as snapshot) queries like range, k-nearest neighbor (kNN), contact, etc. However, having the available models and solutions does not bring them closer for use by domain scientist who may want to explore the impact of the uncertainty on realistic domains such as tracking of animals. In such scenarios, a domain scientist may be interested in getting an idea as to what is the possibility of an animal being within certain distance from a water supply (i.e., range query). Similarly, the domain scientists may be interested in the probability of two atoms being within a certain distance from each other (i.e., alibi query). To enable such analysis, we developed a prototype system that offers: (1) selection of a dataset consisting of ( x, y, t ) points corresponding to discrete locations of the objects' motion; (2) visualization of the uncertainty of that motion under the model of space-time prisms (also referred to as beads); (3) Visualization of the answers to range and alibi queries (and, where applicable, the map of the given area). In this demo paper we describe the basic architecture of our prototype system and discuss its functionalities.